(untitled) (Ágora Journal, 2021)
The article aims to discuss the role of the Brazilian Spiritist Federation from the source Reformador, a spiritist newspaper, which disclosed some criminal cases in which citizens who were followers of Spiritism had to respond for adopting practices considered illegal. The Penal Code of 1890 criminalized spiritist practices in its article 157, which led a number of adherents to respond to criminal proceedings, including the Brazilian Spiritist Federation itself at the time of the establishment of the Sanitary Regulation in 1904, which intensified the persecutions. Based on Pierre Bourdieu’s theoretical-methodological analysis, we understand that criminalization promoted symbolic disputes between the religious field and the field of science, represented by medical professionals. Understanding the spiritists as new players in the above fields, in search of legitimation, they started to be inserted by the political, police and medical authorities in what was legally called charlatanism and medicine. The judges were tasked with differentiating what would be religious and healing in a tangle of speeches in defense of religious freedom and public health.